The Influence of Work Discipline, Leadership Style, and Job Training on Employee Performance at the Makassar Sub-District Office - Kasmuliadi Amir; Rina; Yusram Adi (Jurnal Economic Resource, 2022)
The purpose of this study was to analyze the effects of work discipline, leadership style, and job training on employee performance at the Makassar sub-district office. This research is a type of quantitative descriptive research with a simple correlation analysis approach and multiple linear regression to measure the relationship between variables. The choice of this method was based on the formulation of the problem. The research was carried out at the Makassar sub-district office in August-December 2021. The sample in this study consisted of 50 employees of the Makassar sub-district office, as well as all the employee population of the office. The data analysis technique used a simple linear regression analysis approach with the SPSS 25 program. The results showed that leadership style, work discipline, and training simultaneously had a significant influence on employee performance in Makassar City, Sub-District Makassar.